RETRACTED: Analysis of 9 microsatellite markers in Kalmyk cattle - Chimidova Nadezhda; Ubushieva Altana; Ubushieva Victoria (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001